Effect of irrigation and phosphorus on safflower (Carthamus tinctorius) yield in Rajasthan - Singh, Ved; Ramdev, Ramdev; Sharma, S K; Verma, B L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during winter season of 1990-91, 1991-92 and 1992-93 to study the effect of irrigation andphosphorus levels on yield of safflower (Carrhamus tintortus L. ). Two irrigations applied to safflower either at rosette +flowering or rosette + seed-setting stages gave significantly higher yield (1.52 tonnes/ha), yield attributes (16.7heads/plant and 18.1 seeds/head), net return (Rs 6 340/ha) and benefit : cost ratio (.1.47) compared with l irrigation.Applicatitln 0f 26.4 kg P/ha gave significantly higher seed yield (1.43 tonnes/ha) and oil yield (439 kg/ha) than the controland 13.2 kg P/ha. However, irrigation level did not affect the oil content in seed. Interaction effect irigation and P onseed yield was significant. Application of Â P @ 26.4 kg/ha gave additional net return of Rs 1 095/ha compared with 13.2 kg/haand of Rs 2 470/ha compared with the control. Highest mean consumptive use (377 mm water) was recorded when safflowerreceived 3 irrigations (rosette + flowering + seed-setting stages) and highest water-use efficiency (4.37 kg/ha-mm) wasobtained when 2 irrigations were applied at rosette + seed-setting stages.